Presumed nasolacrimal endometriosis - Turkcuoglu, Ilgin; Turkcuoglu, Peykan; Kurt, Julide; Yildrim, Hanefi (Lippincott Williams & Wilkins, 2008)
A 13-year-old girl was admitted with a complaint of cyclic bleeding from the left inferior punctum with menstruation. Crusted hemorrhage was noticed in the tear meniscus of the left eye and just inferior to the left caruncle. With gradient-echo magnetic resonance imaging, the hemorrhagic tissue in the nasolacrimal canal was demonstrated and the diagnosis of nasolacrimal endometriosis was made. Nasolacrimal endometriosis is a rare ocular condition. Its management and histologic diagnosis remain challenging.